Cold Induction of Arabidopsis CBF Genes Involves Multiple ICE (Inducer of CBF Expression) Promoter Elements and a Cold-Regulatory Circuit That Is Desensitized by Low Temperature - Zarka, Daniel G. (The American Society for Plant Biologists, 2003)
The Arabidopsis CBF1, 2, and 3 genes (also known as DREB1b, c, and a, respectively) encode transcriptional activators that have a central role in cold tolerance. CBF1-3 are rapidly induced upon exposing plants to low temperature, followed by expression of CBF-targeted genes, the CBF regulon, resulting in an increase in plant freezing tolerance. At present, little is known about the cold-sensing mechanism that controls CBF expression. Results presented here indicate that this mechanism does not require a cold shock to bring about the accumulation of CBF transcripts, but instead, absolute temperature is monitored with a greater degree of input, i.e. lower temperature, resulting in a greater output, i.e. higher levels of CBF transcripts. Temperature-shift experiments also indicate that the cold-sensing mechanism becomes desensitized to a given low temperature, such as 4°C, and that resensitization to that temperature requires between 8 and 24 h at warm temperature. Gene fusion experiments identified a 125-bp section of the CBF2 promoter that is sufficient to impart cold-responsive gene expression. Mutational analysis of this cold-responsive region identified two promoter segments that work in concert to impart robust cold-regulated gene expression. These sequences, designated ICEr1 and ICEr2 (induction of CBF expression region 1 or 2), were also shown to stimulate transcription in response to mechanical agitation and the protein synthesis inhibitor, cycloheximide.